Odor learning in Microplitis mediator (Hymenoptera: Braconidae) is mediated by sugar type and physiological state - Luo, Shuping; Michaud, J. P.; Li, Jiancheng; Liu, Xiaoxia; Zhang, Qingwen (My University, 2013)
Parasitoids can be conditioned to respond to novel odors through associative learning, and learning can be sensitive to physiological state. This study examined the effects of various types of sugar, and two physiological factors, mating status and oviposition experience, on odor learning in the parasitoid Microplitis mediator Haliday. Female M. mediator exhibited prolonged feeding periods on fructose, glucose and sucrose, whereas periods of feeding on raffinose, mannose and galactose were not different from water. Mating status did not affect feeding time on any sugars, but the conditioned response to eucalyptol was stronger in mated females than in virgins when the unconditioned stimulus was glucose. When females were conditioned to both food- and host-associated odors and then given a choice between them in a Y-tube olfactometer, hungry females prefered the former and satiated females, the latter, regardless of whether they had prior oviposition experience. However, oviposition experience shifted the preference of partially fed females in favor of the host-associated odor, whereas those without such experience preferred the food-associated odor. This finding suggests that parasitoid females in intermediate hunger states might be more responsive in tests of other experience effects than either starved or fully fed ones.
Citation: Luo, S., Michaud, J. P., Li, J., Liu, X., & Zhang, Q. (2013). Odor learning in Microplitis mediator (Hymenoptera: Braconidae) is mediated by sugar type and physiological state. Retrieved from http://krex.ksu.edu
Keywords: Gustatory response; Sugar type; Physiological state; Learning; Hunger state; Ovipositional experience; Parasitoid